THE ANTI-CORROSION STRENGTH OF THE RENEWED SULFUR CONCRETE (Scientific journal of the Fergana State University, 2025)
In this article, it was found expedient to obtain sulfur concrete based on organic nitrogen-containing compounds. Melamine, hydrazine, 2,4-dinitrophenylhydrazine, and bitumen were used as modifiers. The corrosion resistance of the obtained samples of sulfur concrete was studied in aggressive environments, including: 10% solutions of acids H2SO4, HCl, HNO3, H3PO4, 3% solutions of Na2SO4, NaCl, NaF, 10% NaOH, pH=4-10 and machine oil, dichloroethane and diesel fuels. The results obtained in the course of research show an increase in corrosion resistance and an improvement in the mechanical properties of sulfur concrete.